1993
DOI: 10.1016/s0040-4020(01)86262-1
|View full text |Cite
|
Sign up to set email alerts
|

Molecular recognition of creatinine

Abstract: Ein erster Versuch, den Analyten mit Hilfe eines 4-Aminoacridin-5-yl-amino-substituierten 4(3H)-Pyrimidons nicht nur durch drei, sondern durch vier Wasserstoffbriicken an den Wirt zu binden, misslang. Der Grund dazu liegt wahrscheinlich in der zu grossen Flexibility dieser Wirtverbindung. Unter Beriicksichtigung dieser Tatsache wird ein neues Wirtmolekul vorgeschlagen. Seine Fahigkeit, Kreatinin zu komplexieren, wurde mit Hilfe von Kristallstrukturdaten sowie eines Molecular Modelling-Programmes und quantenmec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
20
0

Year Published

1995
1995
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 43 publications
0
20
0
Order By: Relevance
“…[6][7][8][9][10][11] On the other hand, ionselective electrodes (ISEs) are among the simplest and most robust gauges of ion concentration that are already in use in routine clinical laboratories. [12] Thekey hurdle in the development of ISEs for relatively complex analytes,s uch as creatinine,i st he availability of "ionophores", synthetic receptors that preferentially bind the target molecule.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[6][7][8][9][10][11] On the other hand, ionselective electrodes (ISEs) are among the simplest and most robust gauges of ion concentration that are already in use in routine clinical laboratories. [12] Thekey hurdle in the development of ISEs for relatively complex analytes,s uch as creatinine,i st he availability of "ionophores", synthetic receptors that preferentially bind the target molecule.…”
mentioning
confidence: 99%
“…In contrast to its synthetic flat ("two-dimensional") predecessors, [6][7][8][9][10][11] receptor 1 has at hree-dimensional shape and includes the creatinine guest 2 in its aromatic polar cavity by surrounding most of its surface.T he aromatic cavity of 1 is functionalized with as ingle phosphonate group at its open end and four pyrrole NH moieties at the closed end. These polar groups offer complementary hydrogen-bonding interactions to the polar functions of the included guest.…”
mentioning
confidence: 99%
“…[6][7][8][9][10][11] Accordingly, we have designed a monomer 1 containing one isocytosine unit at each end of an enantiomerically pure C 2 -symmetric angle bar, the bicyclo-[3.3.1]nonane system ( Figure 1, bottom left). Molecular modeling at the semi-empirical level (see the Supporting Information) indicated that a cyclic tetramer 1 4 is favored and that its quadratic cavity would have a width of approximately 13 from face to face in hetero-and homotautoleptic aggregation ( Figure 3).…”
mentioning
confidence: 99%
“…[6][7][8][9][10][11] Accordingly, we have designed a monomer 1 containing one isocytosine unit at each end of an enantiomerically pure C 2 -symmetric angle bar, the bicyclo-[3.3.1]nonane system ( Figure 1, bottom left). [6][7][8][9][10][11] Accordingly, we have designed a monomer 1 containing one isocytosine unit at each end of an enantiomerically pure C 2 -symmetric angle bar, the bicyclo-[3.3.1]nonane system ( Figure 1, bottom left).…”
mentioning
confidence: 99%